2019
DOI: 10.3946/kjme.2019.146
|View full text |Cite
|
Sign up to set email alerts
|

The attitudes of Korean medical students toward patient safety

Abstract: PurposeThis study investigated the attitudes of Korean medical students about patient safety to determine which perspectives required increased focus in terms of educational development.MethodsAttitudes were assessed using the Patient Safety Questionnaire, a tool designed to measure attitudes toward patient safety among medical students. Questionnaires were distributed to 580 clinical year students across four medical schools in December 2018.ResultsA total of 300 returned questionnaires were used in the final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 7 publications
0
25
0
2
Order By: Relevance
“…Of these, 157 studies were excluded for various reasons, such as mismatch with the inclusion criteria, wrong study design (e.g., validation study, quasi-experimental design), mixed population, wrong focus of the study, or full text not available (see Supplementary File 3 ). Finally, 31 studies meeting the inclusion criteria were included [ 13 , 20 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] (see Supplementary File 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 157 studies were excluded for various reasons, such as mismatch with the inclusion criteria, wrong study design (e.g., validation study, quasi-experimental design), mixed population, wrong focus of the study, or full text not available (see Supplementary File 3 ). Finally, 31 studies meeting the inclusion criteria were included [ 13 , 20 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] (see Supplementary File 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…In all included studies, the sampling strategy was relevant to address the research question. In more than two thirds of the studies, the study sample was clearly described and representative of the target population [ 13 , 20 , 23 , 24 , 25 , 26 , 28 , 30 , 31 , 32 , 33 , 34 , 35 , 37 , 38 , 39 , 40 , 42 , 43 , 45 , 47 , 48 , 49 , 50 ], the risk of non-response bias low [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 30 , 31 , 33 , 35 , 36 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 48 , 49 ], and the statistical analysis appropriate to answer the research question [ 13 , 20 , 22 , 24 , 25 , 27 ,…”
Section: Resultsmentioning
confidence: 99%
“…This should alert medical educators to involve patient safety in their future curricula. Other studies also found medical students to be positive towards the inclusion of patient safety contents in the curricula [11,[50][51][52][53]. However, despite the importance they felt for inclusion of patient safety contents in the curricula, the majority of students found that patient safety was mainly learned in clinical practice, rather than in lecture rooms.…”
Section: Discussionmentioning
confidence: 99%
“…Even though Carruthers et al used a Likert scale of 1–7, some studies have used the Likert scale of 1–5 [ 17 , 18 ]. In this study, the items were measured on a scale of 1–5, where a response of 1 indicated disagreement while a response of 5 indicated agreement to the statement.…”
Section: Methodsmentioning
confidence: 99%
“…While positive experiences enhance patient safety, negative experiences may lead to more harm to the patients. Even though many researches had been conducted elsewhere on medical students' attitudes towards patient safety [11][12][13][14][15][16][17][18], such a study is yet to be conducted in Malaysia. Studies conducted in the USA, Pakistan, Korea, Singapore, and Hong Kong have shown inadequate awareness of medical error reporting.…”
Section: Introductionmentioning
confidence: 99%